Analisis Perubahan Organoleptik Onde-Onde Ubi Ungu dengan Penyimpanan pada Suhu Ruang dan Suhu Chiller: Penelitian - Yuli Astuti; Romy Athaya Arzaky (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Onde-onde is a popular traditional food, including variants made from purple sweet potato, which is rich in antioxidants. However, its perishable nature requires appropriate storage strategies to maintain quality. This study aimed to analyze the organoleptic changes of purple sweet potato onde-onde during storage at room temperature and chiller temperature. The study was conducted as an observational experimental design using a quantitative descriptive approach. Organoleptic observations included color, aroma, taste, and texture for seven days. Results showed that storage at room temperature caused a more rapid decline in quality, with signs of deterioration appearing as early as day 3 and the product becoming unfit for consumption on days 5–6. Conversely, storage at chiller temperature slowed down deterioration, with the product remaining fit for consumption until days 4–5. It can be concluded that chiller temperature is effective in extending the shelf life of purple sweet potato onde-onde and maintaining its sensory quality. Recommendations are given for product storage at refrigerated temperatures and for product packaging to include shelf life information.